Iron deficiency: an emerging therapeutic target in heart failure. Issue 18 (23rd June 2014) - Cohen-Solal, Alain; Leclercq, Christophe; Deray, Gilbert; Lasocki, Sigismond; Zambrowski, Jean-Jacques; Mebazaa, Alexandre; de Groote, Pascal; Damy, Thibaud; Galinier, Michel
Abstract : In patients with heart failure, iron deficiency is frequent but overlooked, with a prevalence of 30%–50%. Since it contributes to cardiac and peripheral muscle dysfunction, iron deficiency is associated with poorer clinical outcomes and a greater risk of death, independent of haemoglobin level. Therefore, iron deficiency emerges as a new comorbidity and a therapeutic target of chronic heart failure in addition to chronic renal insufficiency, anaemia and diabetes. In a series of placebo-controlled, randomised studies in patients with heart failure and iron deficiency, intravenous iron had a favourable effect on exercise capacity, functional class, LVEF, renal function and quality of life. These clinical studies were performed in the context of a renewed interest in iron metabolism. During the past 10 years, knowledge about the transport, storage and homeostasis of iron has improved dramatically, and new molecules involved in iron metabolism have been described (eg, hepcidin, ferroportin, divalent metal transporter 1). Recent European guidelines recommend the monitoring of iron parameters (ie, serum ferritin, transferrin saturation) for all patients with heart failure. Ongoing clinical trials will explore the benefits of iron deficiency correction on various heart failure parameters.